(untitled) (Academia Science Repository, 2023)
The article tells about the creative heritage of Al-Hakim al-Tirmizi, who was a student of Imam Bukhari, the Sultan of Hadith Studies, and the current activities of the memorial complex and museum, as well as further study of the heritage of our scientists and scientists who grew up in the bosom of our Motherland, will help us become a perfect generation that will serve the development of our country.